Determining Proportional Penalties for Misdemeanor of the Criminal Code Part 3 - Yeeprae, Nuti; Chutinun, Achariya (Suan Dusit Graduate School Academic Journal, 2025)
This research aims to study the problem of imposing criminal penalties for offenses with varying degrees of severity, both serious and minor offenses, under the Thai Criminal Code. This research applied a qualitative research consisting of documentary research. Through the study, it was found that misdemeanors under the Criminal Code, represent minor offenses established in the past without subsequent amendments to align with current circumstances. This has led to issues in applying criminal penalties that are not proportionate and fail to achieve the intended purpose of punishment. In Thailand, despite the Constitution of the Kingdom of Thailand B.E. 2560, Section 77, Paragraph 3, not explicitly providing criteria for determining offenses of a serious nature, a definition of serious offenses has been outlined in accordance with the recommendations of the Law Development Committee in the year B.E. 2562. These guidelines have been utilized in assessing offenses up to the present. However, the pre-existing offenses established before the formulation of these criteria have not been reviewed to assess whether the prescribed measures for penalties are appropriate. This article proposes the application of Germany criteria for assessing serious offenses based on those, to be adopted alongside the criteria suggested by the Thai Law Development Committee. It considering criminal penalties as a last resort. Additionally, it suggests a framework for canceling minor offenses of the criminal code part 3, it proposes converting misdemeanors of a serious nature to criminal offenses in the offense section in order to solve problems for concerning the appropriateness of penalties in alignment with the nature of the offenses and the objectives of punishment under the Thai Criminal Code in future Thai criminal legislation.